Experimental and numerical study of a hydrokinetic turbine based on tandem flapping hydrofoils. (1st May 2019) - Xu, Wenhua; Xu, Guodong; Duan, Wenyang; Song, Zhijie; Lei, Jie
Abstract: The energy harvesting of a hydrokinetic turbine based on tandem flapping hydrofoils is investigated experimentally and numerically. The mechanisms with crankshafts and connecting rods are adopted to convert the oscillatory motions of the hydrofoils into rotary motions. The hind hydrofoil performs oscillatory motion in the vortex flow of the fore hydrofoil. The longitudinal spacing L x between the two hydrofoils is fixed while the phase difference ε between the flapping motions of the two hydrofoils can be shifted from − π to π . The global phase shift Φ, which is the combination of L x, ε and the Strouhal number S t, is adopted to describe the vortex interaction modes. The effects of S t and Φ on the energy harvesting have been tested. Experimental data show that the highest hydrodynamic efficiency of single hydrofoil is 25.2 % at S t = 0.235 . The optimum parameters for the energy harvesting of tandem hydrofoils have been found. The highest hydrodynamic efficiency is found at S t = 0.24 with Φ / 2 π ≈ 0.3 . Numerical simulations are performed to study the vortex interaction modes of these typical cases. The beneficial vortex pattern and the detrimental vortex pattern, which result in the highest and lowest efficiency of the turbine, have been investigated. Highlights: A hydrokinetic turbine based on tandem flapping foils is studied experimentally. The peak efficiency appears at medium Strouhal number and selected phase shift. The beneficial vortex interaction mode is found with global phase shift Φ = 0.6π.